The Effects of Using Kahoot! on Understanding the Concept of Mathematical Symbols in Higher Education - Molli Wahyuni; Mohammad Fauziddin; Lussy Midani Rizki (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research was motivated by the condition of Mathematics Education students who were unfamiliar and unable to read and use these mathematical symbols correctly. This study aimed to examine the effect of Kahoot! game media on students’ understanding of concepts, especially on mathematical symbols. The population of this study was students of the Mathematics Education Study Program at Pahlawan Tuanku Tambusai University. At the same time, the research sample was 100 people obtained through random sampling, namely students who attended the introduction of mathematical symbols. The data was collected by taking a mathematical understanding test before and after using the Kahoot game media. Analysis of the data used was the paired t-test. The results showed a difference in the pre-test and post-test scores of students’ conceptual understanding, where the significance value was 0.05%.